PKM senam otak pada Siswa Sekolah Dasar Negeri Kompleks IKIP 1 Makassar - Nurussyariah Hammado; Sahabuddin Sahabuddin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Brain Gym is a combination of body movement and brain concentration.bywhich the right and the left brain hemisphere is balanced during gradual body movement. Brain gymnastics began as a way to deal with concentrated disorders in hyperactive children, depression, or children with light to moderate brain damage. Currently brain gym can also be applied to elementary school students to help the development of coordination of motor movements and cognitive at the same time. Partners of the Community Partnership Program (PKM) in this situation is SD Negeri Kompleks IKIP I Makassar with the main target is the teacher and students. This partnership program is carried out using the demonstration method. After socializing the program with the school principal and sports teacher, students are given a short practice about the principle of brain gym movements. Several targets to be achieved in this partnership program are 1) the partner understands the purpose brain gym program; 2) partners recognize the form of brain exercise movements; 3) stimulating the interest of partners to actively perform brain gym and 4) making brain gym as one of the exercise programs for elementary school students.